A comparative study to diagnose the accuracy of E-speed film, complimentary metal oxide semiconductor and storage phosphor systems in the detection of proximal caries: An in vitro study - Ramesh, Tatapudi; Upendra, Gurugubelli; Sravani Krishna, Bandaru; Dathar, Sahithi; Sinha, Priyankesh; M.N, Raghavendra; Swathi, Myla; Roja Vara Lakshmi, K (International Journal of Dental Research, 2016)
Background: Dental caries is one of the most commonly encountered conditions in clinical dentistry and these lesions remain undetected when confined to the vicinity of inter-proximal surfaces. Radiography plays a key role in the detection of inter-proximal caries especially in tight contacts.Objectives: The purpose of this study was to compare the diagnostic accuracy of E-speed film, complementary metal oxide semiconductors (CMOS) and storage phosphor systems (PSP) in the detection of proximal caries of the posterior teeth.Methods: Conventional films, CMOS and PSP images were used in detecting proximal caries on mesial and distal surfaces of 63 teeth (126 surfaces). Interpretation of all digital and conventional radiographs were performed and reanalyzed by four observers. The collected data was subjected to statistical analysis using chi square test, weighed kappa statistics and spearman rank correlation coefficient.Results: The PSP images showed more accurate results in identifying normal tooth, enamel caries, dentinal caries and deep dental caries and kappa statistics had represented almost perfect reading of 0.8 – 0.9 for PSP images whereas CMOS images showed substantial reading of 0.6 – 0.7, and for IOPA images it showed moderate reading of 0.5 – 0.6, which stated that the higher inter-observer agreement was obtained for PSP images when compared with images taken by IOPA and CMOS. The intra-observer reliability by kappa statistics had shown highly significant value (0.82) in the present study.Conclusion: Conventional films, CMOS and PSP images had shown almost appropriate results in the detection of proximal caries but PSP receptors were better in disclosing the details more accurately in terms of delineating the actual extent of the lesion pertaining to their high resolution capacity and further their flexibility made them easier during handling the radiograph, when compared with that of rigid CMOS receptors.